T-wave inversions and the role of de-training in the differentiation of athlete’s heart from pathology: is 6 months too long? - Whyte, Gregory (BMJ Case Rep, 2012)
Electrocardiographic changes are common in athletes. Differentiation of a physiological from a pathological substrate is important as ECG changes may indicate underlying cardiac disease placing the athlete at increased risk of sudden cardiac death. Deep T-wave inversions are uncommon in Caucasian athletes however; appear more prevalent in black athletes. Irrespective of the ethnic origin of the athlete, deep T-wave inversions require thorough follow-up. At present, 6 months de-training is recommended to assist in the differentiation of physiologic and pathologic changes where a definitive diagnosis is elusive through standard diagnostic techniques. This case study examines findings from a black and a Caucasian athlete presenting with deep T-wave inversions following a brief (ca.3 week) period of de-training resulting in normalisation of T-wave. These cases suggest that a shorter period of time may be sufficient in differentiating physiological from pathological mechanisms for deep T-wave inversions.